1999
DOI: 10.1007/bf03172973
|View full text |Cite
|
Sign up to set email alerts
|

Feeling of difficulty: An aspect of monitoring that influences control

Abstract: This study aimed at delimiting possible relations of feeling of difficulty (FOD) with control ideas pertaining to a particular task. Participants were 274 students of 7th, 8th, and 9th grade. They were tested with two mathematical tasks; they were also asked to give ratings of the feeling of difficulty at 4 phases: In advance of problem solving, during planning of the solution, after solution production, and an overall estimation. Participants also gave ratings for control ideas such as need to know the rule, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 10 publications
2
44
1
10
Order By: Relevance
“…From this point of view, they provide information about the person's capability to deal with a particular task and achieve a desired outcome. This sense of task-specific competence, however, may have broader effects than just online monitoring and control of processing (Efklides et al, 1999). As Metallidou and Efklides (2001) have shown, ME influence the person's causal attributions of ability, effort, and task difficulty.…”
Section: Metacognitive Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…From this point of view, they provide information about the person's capability to deal with a particular task and achieve a desired outcome. This sense of task-specific competence, however, may have broader effects than just online monitoring and control of processing (Efklides et al, 1999). As Metallidou and Efklides (2001) have shown, ME influence the person's causal attributions of ability, effort, and task difficulty.…”
Section: Metacognitive Experiencesmentioning
confidence: 99%
“…Feeling of difficulty (FOD) reflects processing interruption during problem solving and its role is to trigger control decisions. (For the factors that influence FOD, see Efklides, 2001;Efklides, Papadaki, Papantoniou, & Kiosseoglou, 1997, 1998Efklides, Samara, & Petropoulou, 1999.) Feeling of difficulty is related to the causal attribution of task difficulty (Metallidou & Efklides, 2001) and, therefore, indirectly provides information about the student's capability to deal with the task.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore perceived difficulty should not be confused with objective demands. Efklides, Samara, and Petropoulou (1999) note that although objective task demands and perceived difficulty are often related, they are not perfectly mirrored, as perception depends on various factors, including individual differences in ability, and affect. Bilda et al (2006) suggested that one of the ways that sketching may support the creative process is by reducing strain on working memory resources and by supporting image maintenance.…”
Section: Perceived Difficulty Skill-challenge Balance and Cognitivementioning
confidence: 99%
“…Firstly as Dermitzaki and Efklides (2001) argued, metacognitive experiences form an intrinsic context, mainly affective, that influences the perception of learning outcomes (performance attributions; see also Metallidou & Efklides, 2001) and future motivation and self-regulation in a domain. Secondly, metacognitive experiences trigger control decisions such as effort expenditure and cognitive strategies to be used at the task level (Efklides, Samara, & Petropoulou, 1999). Thirdly, they influence one's self-concept and self-efficacy even without explicit selfevaluative processes (Efklides & Tsiora, Article 2).…”
Section: The Present Special Issuementioning
confidence: 99%